Heap Allocator: Uma Política de Alocação de Máquinas Virtuais em Ambiente de Computação em Nuvens baseada em Heap com Prioridade - Magalhães de Carvalho, Matheus; Vieira, Francisco Mardônio; de Matos, Filipe Fernandes dos Santos; Lopes Gomes, Rafael; Celestino Júnior, Joaquim (Anais do Workshop em Clouds e Aplicações (WCGA); 2019: Anais do XVII Workshop em Clouds e Aplicações, 2019)
Cloud Computing represents a paradigm that provides computing resources on virtual machines that are grouped and allocated according to customer requests. The increasing seeking for this type of service caused an increasing demand for electric energy. Several types of research aim to meet the demand for resources in Cloud Computing, and at the same time, reduce energy consumption in the data center. Within this context, this paper presents a virtual machine allocation policy called Heap Allocator, which mitigates thepower consumption of the data center. A comparative analysis of the proposed solution with other existing mechanisms showed the proposed solution of the data center power consumption by approximately 1: 5%.